Development and application of a 3,000-m Seabed Cone Penetration Test and Sampling System based on a hydraulic drive - Cheng Wang; Lei Guo; Lei Jia; Wenxu Sun; Gang Xue; Xiuqing Yang; Xiaolei Liu (Frontiers in Marine Science, 2024)
The seabed surface is an important boundary for ocean exploration and foundation for ocean engineering construction. Accurate acquisition of seabed sediment mechanical properties and environmental parameters is critical to the development of marine resources and marine engineering. In this study, by designing the Seabed Cone Penetration Test (CPT) and Sampling System, multiparameter in situ testing and low-disturbance sampling of 3,000-m deep-sea seabed sediments are performed. Accounting for the stable penetration speed of the probe rod is the basis for ensuring the accuracy of the static penetration test results. The system adopts electrohydraulic proportional position control and a fuzzy proportional integral derivative (PID) controller to precisely control the position of the piston of the hydraulic circuit, which can improve the accuracy of the cone test data and reduce the interference of the sampling tube with the original sediment during the sampling process. Moreover, electrohydraulic co-simulation of the hydraulic control system was conducted with the AMESim and Simulink software, and the position control and speed control effects of the system were verified. The entire system was tested on site in the Shenhu Sea area of the South China Sea. This test successfully obtained nine in situ parameters, including physical and chemical parameters, for sediments within a depth range of 2.66 m on the seabed surface at a depth of 1,820 m. This system accurately and efficiently reflects the property characteristics of seafloor sediments in an in situ environment and can be widely used in marine engineering geological investigations.